Effects of herbicides and tillage practices on weeds and summer mungbean (Vigna radiata) in wheat (Triticum aestivum)-mungbean cropping sequence - NATH, C P; DAS, T K; RANA, K S (The Indian Journal of Agricultural Sciences, 2016)
A field experiment was conducted at ICAR-Indian Agricultural Research Institute to study the weed management strategy in zero-tillage (ZT) and conventional tillage (CT) with and without residue during 2014 and 2015 in summer mungbean [Vigna radiata (L.) Wilczek] following residual effects of 4 weed control treatments, comprising of readymix and sequential application of herbicides during previous rabi seasons, 2013-14 and 2014-15 in wheat (Triticum aestivum). Previous season weed-control treatment significantly reduced the broad-leaved, narrow-leaved and total weed population and dry weight in both the years over unweeded control. However, herbicidal treatments did not differ significantly adopted during previous rabi season. Results showed that ZT with residue retention (ZT+R) caused a significant reduction in population and dry weight of weeds compared to CT without residue. Mungbean yield attributes were higher in ZT with residue retention (ZT+R) than conventional-tilled treatments. Previous applied of pendimethalin 1 kg/ha followed by sulfosulfuron 25 g/ha combined with ZT with 5 tonnes/ha residue retention (ZT+R) +75% N + rest N based on GreenSeekerTM (GS) resulting in higher mungbean yield, may be recommended for mungbean production in north-western Indo-Gangetic plains of India in wheat-mungbean sequence.